c-Myc Upregulated by High Glucose Inhibits HaCaT Differentiation by S100A6 Transcriptional Activation - Zhang, Jie; Yang, Peilang; Liu, Dan; Gao, Min; Wang, Jizhuang; Wang, Xiqiao; Liu, Yan; Zhang, Xiong (Frontiers in Endocrinology, 2021)
Keratinocyte differentiation dysfunction in diabetic skin is closely related to impaired skin barrier functions. We investigated the effects of c-Myc and S100A6 on Human immortal keratinocyte line (HaCaT) or keratinocyte differentiation and potential mechanisms. The expression levels of differentiation makers such as transglutaminase 1(TGM1), loricrin (LOR), and keratin 1(K1) were significantly reduced, while the expression of c-Myc was significantly increased in HaCaT cells cultured in high glucose and wound margin keratinocytes from diabetic rats and human patients. Overexpression of c-Myc caused differentiation dysfunction of HaCaT, while knocking down c-Myc promoted differentiation. High glucose increased the expression of c-Myc and inhibited differentiation in HaCaT cells by activating the WNT/β-catenin pathway. Moreover, inhibition of c-Myc transcriptional activity alleviated the differentiation dysfunction caused by high glucose or overexpression of c-Myc. c-Myc binds to the S100A6 promoter to directly regulate S100A6 expression and high glucose promoted S100A6 transcription. The expression of S100A6 was increased in HaCaT cultured with high glucose and wound margin keratinocytes from diabetic rats and human patients. However, the expression of S100A6 was decreased during normal HaCaT differentiation. HaCaT cells treated with S100A6 recombinant protein showed differentiation dysfunction. The expressions of TGM1, LOR and K1 in knockdown S100A6 HaCaT cells were higher than those in the control group. Overexpression of c-Myc or high glucose caused differentiation dysfunction of HaCaT cells, and was rescued by knocking down S100A6. These findings illustrate a new mechanism by which c-Myc upregulated by high glucose inhibits HaCaT differentiation by directly activating S100A6 transcription. Thus, c-Myc and S100A6 may be potential targets for the treatment of chronic diabetic wounds.